Iodised Salt Consumption of Primary School Students and Iodine Concentration in Household Salt - Boonpor, Jirapitcha; Surasiang, Ruethaithip; Thunyasirinon, Chuleewan (Journal of Nutrition Association of Thailand (Online), 2022)
The purpose of this cross-sectional descriptive study was to examine iodised salt consumption in primary school students at grade 4-6 in Chaingkhruea sub district, Sakon Nakhon Province, and to determine iodine concentration in household salt. Subjects consist of 104 students. Data was collected by using questionnaires. Household salts, 104 samples, were collected from kitchens in students’ houses. Statistics used for data analysis was frequency, percentage, mean and standard deviation. Iodine concentration was performed by titration method. The result showed that most students were female (53.8 %) and studied at grade 5 (36.5 %). Students’ GPA was at a good level (74.0 %). Their parents were farmers (48.1 %). Students’ knowledge about iodine for their health was in the medium level (51.9 %). Iodised salt consumption was at 36.5 % of the total students. Household salt was stored in the containers with covers at 60.6 % of total students’ households. Factors including sex, age, GPA and parent occupation were not associated with iodised salt consumption. Students’ knowledge about iodine for their health was significant associated with iodised salt consumption (P<0.05). Students’ family consumed iodised salt in the recommendation range of 20 – 40 milligrams per kilogram (ppm) was only 12.5 % of total households. The average concentration of iodine in household salt was at 17.7 milligrams per kilogram.